PENERAPAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI WUJUD ZAT DAN PERUBAHANNYA DI KELAS IV SDN TLOGOPRAGOTO - Alip Yekti Sumarah; Rintis Rizkia Pangestika; Titi Anjarini (STKIP Subang, 2024)
This research aims to: 1) Describe the implementation of the Guided Inquiry learning model, 2) Determine the increase in student engagement, and 3) Determine the improvement in student learning outcomes on the topic of the states of matter and their changes in grade IV at SDN Tlogopragoto in the 2024/2025 academic year. This study uses a Classroom Action Research (CAR) approach, conducted in two cycles, with each cycle consisting of two meetings. Data collection techniques include observation, interviews, and tests. Data analysis techniques involve both qualitative and quantitative analysis. The research results show that: 1) The implementation of the Guided Inquiry learning model was well-executed, as evidenced by the increase in the percentage of instructional implementation from 86% in cycle I to 100% in cycle II for both teachers and students; 2) The implementation of this model also significantly increased student engagement, with the percentage of active students rising from 35% in the pre-cycle stage to 77.5% in cycle II, indicating an improvement from low to very active; 3) The implementation of the Guided Inquiry learning model improved student learning outcomes on the topic of the states of matter and their changes, as shown by the increase in the percentage of students scoring above the Minimum Mastery Criterion (KKTP) from 25% in the pre-cycle stage to 75% in cycle I, and then to 87.5% in cycle II, with good classification. This research aims to: 1) Describe the implementation of the Guided Inquiry learning model, 2) Determine the increase in student engagement, and 3) Determine the improvement in student learning outcomes on the topic of the states of matter and their changes in grade IV at SDN Tlogopragoto in the 2024/2025 academic year. This study uses a Classroom Action Research (CAR) approach, conducted in two cycles, with each cycle consisting of two meetings. Data collection techniques include observation, interviews, and tests. Data analysis techniques involve both qualitative and quantitative analysis. The research results show that: 1) The implementation of the Guided Inquiry learning model was well-executed, as evidenced by the increase in the percentage of instructional implementation from 86% in cycle I to 100% in cycle II for both teachers and students; 2) The implementation of this model also significantly increased student engagement, with the percentage of active students rising from 35% in the pre-cycle stage to 77.5% in cycle II, indicating an improvement from low to very active; 3) The implementation of the Guided Inquiry learning model improved student learning outcomes on the topic of the states of matter and their changes, as shown by the increase in the percentage of students scoring above the Minimum Mastery Criterion (KKTP) from 25% in the pre-cycle stage to 75% in cycle I, and then to 87.5% in cycle II, with good classification.